MENINGKATKAN PELAYANAN BELL AMBASADOR ( STUDI KASUS DI HOTEL X DI NUSA DUA - Grace, Gabriela; Darmaputra, Putu Gede Eka; Putra, Dewa Gede (Journal of Hospitality Accommodation Management (JHAM), 2025)
This research aims to analyze the improvement of handling guests' luggage upon arrival at Hotel X in Nusa Dua. The study employs a descriptive qualitative method and reveals that out of 16 criteria in the hotel's Standard Operating Procedure (SOP), only 10 criteria have been implemented according to standards. In comparison, the remaining 6 criteria are not yet fully compliant. To address these shortcomings, key indicators are used as a reference: avoiding damage, preventing loss, ensuring items are not misplaced, and avoiding delays in delivery during the arrival phase. The improvements focus on strengthening security measures for luggage, proper placement, and better documentation. This data indicates that the implementation of improved procedures will enhance the quality of service at the hotel